Inhibition of corrosion on API 5L X52 pipeline steel in acid media by Tradescantia spathacea - Rodríguez-Torres, Adriana; Valladares-Cisneros, María Guadalupe; Chávez-Díaz, German; Martínez-Calzada, Víctor; Saldaña-Heredia, Alonso (Frontiers in Chemistry, 2024)
The concentration effect of Tradescantia spathacea (T. spathacea) as corrosion inhibitor of API 5L X52 steel in 0.5 M of H2SO4 was studied here through electrochemical and gravimetric techniques. To achieve it, samples of the material were prepared to be submitted to each of the tests. Results from electrochemical impedance spectroscopy (EIS) showed that there was an optimum concentration of the inhibitor in which is reached the maximum inhibition efficiency, displaying the best inhibition characteristics for this system with a maximum inhibition of 89% by using 400 ppm. However, the efficiency decreased until 40% when the temperature was increased to 60°C. Potentiodynamic polarization curves (PDP) revealed that some of the present compounds of T. spathacea may affect anodic and cathodic process, so it can be classified as a mix-type corrosion inhibitor for API 5L X52 in sulfuric acid. Also, this compound followed an adsorption mechanism; this can be described through a Frumkin isotherm with an adsorption standard free energy difference (ΔG°) of −56.59 kJmol−1. Metal surface was studied through scanning electron microscope, results revealed that by adding inhibitor, the metal surface is protected; also, they evidenced low damages compared with the surface with no inhibitor. Finally, Tradescantia spathacea inhibited the corrosion process with 82% efficiency.